(untitled) (Revista Angelus Novus, 2022)
This article aims to present and explore the demographic profile of sole women (single, widows and married with an absent husband) in the city of São Paulo, through the use of a nominative lists of inhabitants from 1802, inserting these individuals in the synchronic socio-historical context to understand not only their quantitative situation in the population, but also their role in society, with a greater focus on single women. Thus, the study has a quantitative and qualitative basis, relying on the use of documentary sources for the collection of demographic data and bibliographic sources for theoretical-methodological foundations and for the analysis of the quantitative results obtained. The data collected showed that this population niche occupied a very significant portion of the total population, with active economic participation and transformative historical performance.